Mutilations Due to Medical Disorders in Children - Palácios, J (2003)
Soft-tissue and bone necrosis, although rare in childhood, occasionally occur in the course of infectious diseases, either viral or bacterial, and seem to be the result of hypoperfusion on a background of disseminated intravascular coagulation. Treatment consists in correction of septic shock and control of necrosis. Necrosis, once started, shows extraordinarily rapid evolution, leading to soft-tissue and bone destruction and resulting in anatomic, functional, psychological, and social handicaps. Ten mutilated children were treated from January 1986 to January 1999 in Hospital de Dona Estefaˆ nia, Lisbon, Portugal. One was recovering from hemolytic-uremic syndrome with a severe combined immunodeficiency, another malnourished, anemic child had malaria, and three had chicken pox (in one case complicated by meningococcal septicemia). There were three cases of meningococcal and two of pyocyanic septicemia (one in a burned child and one in a patient with infectious mononucleosis). The lower limbs (knee,leg, foot) were involved in five cases, the face (ear, nose, lip) in four, the perineum in three, the pelvis (inguinal region, iliac crest) in two, the axilla in one, and the upper limb (radius, hand) in two. Primary prevention is based on early recognition of risk factors and timely correction. Secondary prevention consists of immediate etiologic and thrombolytic treatment to restrict the area of necrosis. Tertiary prevention relies on adequate rehabilitation with physiotherapy and secondary operations to obtain the best possible functional and esthetic result.